Cluster randomized controlled trial of a peer support program for people with diabetes: study protocol for the Australasian peers for progress study - Riddell Michaela A; Renwick Carla; Wolfe Rory; Colgan Stephen; Dunbar James; Hagger Virginia; Absetz Pilvikki; Oldenburg Brian (BMC, 2012)
Abstract Background Well managed diabetes requires active self-management in order to ensure optimal glycaemic control and appropriate use of available clinical services and other supports. Peer supporters can assist people with their daily diabetes self-management activities, provide emotional and social support, assist and encourage clinical care and be available when needed. Methods A national database of Australians diagnosed with type 2 diabetes is being used to invite people in pre-determined locations to participate in community-based peer support groups. Peer supporters are self-identified from these communities. All consenting participants receive diabetes self-management education and education manual prior to randomization by community to a peer support intervention or usual care. This multi-faceted intervention comprises four interconnected components for delivering support to the participants. (1) Trained supporters lead 12 monthly group meetings. Participants are assisted to set goals to improve diabetes self-management, discuss with and encourage each other to strengthen linkages with local clinical services (including allied health services) as well as provide social and emotional support. (2) Support through regular supporter-participant or participant-participant contact, between monthly sessions, is also promoted in order to maintain motivation and encourage self-improvement and confidence in diabetes self-management. (3) Participants receive a workbook containing diabetes information, resources and community support services, key diabetes management behaviors and monthly goal setting activity sheets. (4) Finally, a password protected website contains further resources for the participants. Supporters are mentored and assisted throughout the intervention by other supporters and the research team through attendance at a weekly teleconference. Data, including a self-administered lifestyle survey, anthropometric and biomedical measures are collected on all participants at baseline, 6 and 12 months. The primary outcome is change in cardiovascular disease risk using the UKPDS risk equation. Secondary outcomes include biomedical, quality of life, psychosocial functioning, and other lifestyle measures. An economic evaluation will determine whether the program is cost effective. Discussion This manuscript presents the protocol for a cluster randomized controlled trial of group-based peer support for people with type 2 diabetes in a community setting. Results from this trial will contribute evidence about the effectiveness of peer support in achieving effective self-management of diabetes. Trial registration number Australian New Zealand Clinical Trials Registry (ANZCTR); ACTRN12609000469213